2000
DOI: 10.1002/1096-8628(20000814)93:4<320::aid-ajmg12>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Clinical manifestations in a large hereditary hemorrhagic telangiectasia (HHT) type 2 kindred

Abstract: HHT type 2 (HHT 2) is a multi-system vascular dysplasia caused by a mutation in the ALK-1 gene, but the phenotype has not been well defined. We report on 51 members of an HHT 2 kindred with an ALK-1 gene mutation shown to be associated with the disorder. This ALK-1 mutation was detected in 38 kindred members who were evaluated systematically for associated vascular abnormalities. Pulmonary arteriovenous malformations (AVMs) were found in 6% of those screened, cerebral AVM in 7%, hepatic AVM in 17%, and spinal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
0
8

Year Published

2001
2001
2018
2018

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(67 citation statements)
references
References 29 publications
2
57
0
8
Order By: Relevance
“…A significantly higher liver involvement had also been reported previously for two large HHT2 families (McDonald et al, 2000;Lin et al, 2001). The main objective of the present study is to screen systematically for mutations in the ENG and ALK1 genes of patients with HHT and liver involvement as compared to patients with HHT and no liver disease.…”
Section: Introductionsupporting
confidence: 78%
See 3 more Smart Citations
“…A significantly higher liver involvement had also been reported previously for two large HHT2 families (McDonald et al, 2000;Lin et al, 2001). The main objective of the present study is to screen systematically for mutations in the ENG and ALK1 genes of patients with HHT and liver involvement as compared to patients with HHT and no liver disease.…”
Section: Introductionsupporting
confidence: 78%
“…Our results are well in accordance with previous publications on hepatic manifestations in patients with HHT. Although liver involvement was reported for a few patients with ENG mutations, (Berg et al, 2003;Harrison et al, 2003;Cymerman et al, 2003;Shovlin et al, 1997) it was much more often reported for patients carrying mutations in the ALK1 gene (Johnson et al, 1996;Piantanida et al, 1996;Berg et al, 1997;McDonald et al, 2000;Lin et al, 2001;Trembath et al, 2001;Olivieri et al, 2002;Abdalla et al, 2003a & b ;Berg et al, 2003). Liver involvement was not routinely assessed in most of these studies, since the emphasis was mainly on the genotype and not the phenotype, or the reports were on multiple family members and not on unrelated individuals.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…17,18 Mutations are distributed throughout the ALK-1 gene. Frameshift and nonsense mutations predict nonsense mediated mRNA decay 27 and failure to produce functional protein.…”
Section: Alk-1 Missense Mutations In Kinase Domainmentioning
confidence: 99%